One piece of paper the simple approach to powerful, personal leadership - Figliuolo, Mike, 1970- (Jossey-Bass, 2011)
"A robust, authentic model for creating and clearly articulating a personal leadership philosophyBased on leadership expert Mike Figliuolo's popular "Leadership Maxims" training course, One Piece of Paper teaches decisive, effective leadership by taking a holistic approach to defining one's personal leadership philosophy. Through a series of simple questions, readers will create a living document that communicates their values, passions, goals and standards to others, maximizing their leadership potential. Outlines a clear approach for identifying a concise and meaningful set of personal leadership maxims by which leaders can live their lives Explains and applies four basic aspects of leadership: leading yourself, leading the thinking, leading your people, and leading a balanced life Generates a foundational document that serves as a touchstone for leaders and their teams Simple, applicable, and without pretense, One Piece of Paper provides a model for real leadership in the real world"--